COUNTING GAME APPLICATION FOR KINDERGARTEN CHILDREN - Teri Ade Putra; Raja Ayu Mahessya; Yesri Elva; Pradani Ayu Widya Purnama (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
Problems The development of Information Technology plays an important role in human life. With the development of Information Technology, humans can easily get information and humans can easily carry out daily activities with the help of existing technology. Technology brings people to see the outside world further, open their minds to think, and build creativity to create new things, one of the technologies that is currently developing very rapidly is smartphone-based technology, especially Android. Many android applications are very helpful at this time such as health applications, transportation and there are also educational games. Educational games can make it easier to learn, sometimes when learning someone will be faced with conditions where it is difficult to understand the lesson, so with the educational game it is hoped that it can help users understand the lessons in the game, besides that educational games are a very fun learning tool for students. , because students will be happier and easier to understand by playing while learning